New Student Admission Information System At Amik Wahana Mandiri - Effendi, Rustam; Efendi, Yasin (Teknik Informatika Fakultas Ilmu Komputer, 2022)
In an increasingly advanced era like today computers have become an inseparable part of human life. The role of computers has been felt in almost all areas of life, especially along with the rapid development of computer network technology, all the information we need can be obtained in just a short time. One of them is through the internet network, there are various information in it. The Internet is a global computer network that is interconnected through telecommunications lines. AMIK Wahana Mandiri, as a formal higher education institution that concentrates on informatics and computer management has the task of improving the competence,activities, and professionalism of students to be able to compete globally after completing their education at AMIK Wahana Mandiri. In this study , we will discuss the web-based information system fornew AMIK Wahana Mandiri students. This system is an application system to manage new student data and as a medium to see various information about new student admissions at AMIK Wahana Mandiri which can be accessed anytime and anywhere (online). The system is designed using the UML (Unified Modelling Language) modeling language and implemented using PHP, Apache Web Server and MySQL Server. The research methods used are literature, observation, interviews, analysis, design, trial and implementation. The conclusion of this study is that it is hoped that a web-based new student admission information system can be built.